The Meaning of Nyangahatn Ritual of Dayak Kanayatn Community for Disaster Mitigation - Mohammad Maulana Magiman; Sulistyo, Ary; Jeanne Francoise (International Journal of Culture and Art Studies, 2021)
This research focused on the Nyangahatn ritual in Dayak Kanayatn indigenous people in West Kalimantan. This study uses a descriptive qualitative research method with a phenomenological approach with an emphasis on literature study. This paper uses the cultural theory, human ecology, and Disaster Mitigation and shows that there is a connection between those theories in Nyangahatn people’s rituals. Nyangahatn ritual related to the cultivation practices carried out based on the rice planting cycle. The results showed that the Nyangahatn ritual is a pearl of local wisdom, which is an effort in mitigating and adapting to disasters, especially regarding the planting and harvesting seasons. Forests or land cleared for cultivation are very calculated to avoid degradation and air sources. The Kanayatn Dayak indigenous people are very understanding about natural signs. In the process of land clearing for agriculture, it is essential to consider the land area is to be planted so that it does not disturb the forest ecosystem. Meanwhile, the culture of balale' or gotong royong as a form of solidarity and harmony between community members is still maintained.